2022
DOI: 10.1186/s41043-022-00312-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to breastfeeding are shaped by sociocultural context: an exploratory qualitative study in Bangladesh

Abstract: Background Breastfeeding practice is still not optimum in Bangladesh. Understanding barriers to breastfeeding is needed to prevent harmful practices. This study aimed to understand barriers to breastfeeding among infants and young children in Bangladesh. Methods This qualitative study was conducted in five rural sub-districts and one urban slum in Bangladesh. We conceptualized that barriers to breastfeeding can be broadly grouped into individual, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Scaling up breastfeeding: the benefits of breastfeeding for a healthier weight and postpartum weight loss have been well-documented [86,107,108]. However, breastfeeding practice is still not optimum in Bangladesh, and women face a range of barriers at the individual, societal, and system levels that include adverse effects of breastfeeding on maternal health, nutrition and physical appearance [109]. Proven interventions for scaling up breastfeeding in Bangladesh and other Asian countries, which combined intensified interpersonal counseling, mass media campaigns, and community mobilization interventions [110], need to be implemented not only for ensuring nutrition for children but also as an effective approach for healthy BMI for women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%
“…Scaling up breastfeeding: the benefits of breastfeeding for a healthier weight and postpartum weight loss have been well-documented [86,107,108]. However, breastfeeding practice is still not optimum in Bangladesh, and women face a range of barriers at the individual, societal, and system levels that include adverse effects of breastfeeding on maternal health, nutrition and physical appearance [109]. Proven interventions for scaling up breastfeeding in Bangladesh and other Asian countries, which combined intensified interpersonal counseling, mass media campaigns, and community mobilization interventions [110], need to be implemented not only for ensuring nutrition for children but also as an effective approach for healthy BMI for women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%
“…Pilot testing was conducted with 20 participants who were similar to the study's population to ensure the questionnaire's validity and reliability. The results of the pilot testing indicated that the observation sheet was valid and reliable for use [8], [9].…”
Section: Methodsmentioning
confidence: 92%
“…Despite various efforts to raise awareness of the importance of EBI, there are often still obstacles to its practice in the form of sociocultural aspects that cause the implementation of EBI to be hampered [8], [9]. As also happened in one district in Indonesia, the problem of low EBI rates in West Tulang Bawang Regency, Lampung Province, is reflected in the achievement of an EBI of 8.74%.…”
Section: Introductionmentioning
confidence: 99%
“…Scaling up breastfeeding: the benefits of breastfeeding for a healthier weight and postpartum weight loss have been well-documented [86,114,115]. However, breastfeeding practice is still not optimum in Bangladesh, and women face a range of barriers at the individual, societal, and system levels that include adverse effects of breastfeeding on maternal health, nutrition, and physical appearance [116]. Proven interventions for scaling up breastfeeding in Bangladesh and other Asian countries, which combined intensified interpersonal counseling, mass media campaigns, and community mobilization interventions [117], need to be implemented not only for ensuring nutrition for children but also as an effective approach for healthy BMI for women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%